2013
DOI: 10.1371/journal.pone.0074011
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of the Mitochondrial Proteomes of Drosophila melanogaster Adapted to Extreme Oxygen Conditions

Abstract: Mitochondria are the primary organelles that consume oxygen and provide energy for cellular activities. To investigate the mitochondrial mechanisms underlying adaptation to extreme oxygen conditions, we generated Drosophila strains that could survive in low- or high-oxygen environments (LOF or HOF, respectively), examined their mitochondria at the ultrastructural level via transmission electron microscopy, studied the activity of their respiratory chain complexes, and quantitatively analyzed the protein abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…We compared our results with the Drosophila mitochondrial proteome obtained in two previous studies (16,17) that identified proteins from whole mitochondria, including matrix, both mitochondrial membranes, and intermembrane space, following traditional mitochondrial isolation (Fig. 4 E and F and Fig.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…We compared our results with the Drosophila mitochondrial proteome obtained in two previous studies (16,17) that identified proteins from whole mitochondria, including matrix, both mitochondrial membranes, and intermembrane space, following traditional mitochondrial isolation (Fig. 4 E and F and Fig.…”
Section: Significancementioning
confidence: 99%
“…S7). Yin et al (16) identified 718 proteins corresponding to 698 genes based on the FlyBase release 5.54 gene annotation; 49% of these were represented in our positive control list, and 9% were in our negative control list. In addition, Lotz et al (17) identified 1,089 proteins, of which 57% were in our positive control list.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…PPIF is the most studied MPT regulator, and a Drosophila homolog (Cyp-1) has been isolated in multiple proteomic studies of purified Drosophila mitochondria (18,19) (Fig. S2A).…”
Section: +mentioning
confidence: 99%
“…However, mRNA levels are not always correlated closely with protein abundance and function in living systems (de Sousa Abreu et al, 2009;Foss et al, 2011;Gry et al, 2009;Nie et al, 2007;Pascal et al, 2008;Yin et al, 2013). Therefore, recent research efforts have involved characterizing global patterns of protein expression of BAT across the circannual cycle in hibernators using various proteomics techniques.…”
Section: Bat Proteomicsmentioning
confidence: 99%